Nanoscopic materials : size-dependent phenomena - Roduner, E. 1947- (RSC nanoscience & nanotechnology., 2006)
Nanotechnology has been hailed as a key technology of the 21st century. This book focuses on a qualitative and quantitative approach, discussing all areas of nanotechnology with particular emphasis on the underlying physico-chemical and physical principles of nanoscience.